Recent advances in lead-free dielectric materials for energy storage. (May 2019) - Zou, Kailun; Dan, Yu; Xu, Haojie; Zhang, Qingfeng; Lu, Yinmei; Huang, Haitao; He, Yunbin
Graphical abstract: Diagram of power density as a function of energy density in different energy-stored devices. Highlights: Dielectric capacitors have fast charge/discharge rate, and high power density. No review about energy storage properties in lead-free materials has been reported. We focus on the recent progress of various lead-free materials for energy storage. Strategies are proposed to improve energy storage capacity of lead-free materials. Abstract: To better promote the development of lead-free dielectric capacitors with high energy-storage density and efficiency, we comprehensively review the latest research progress on the application to energy storage of several representative lead-free dielectric materials, including ceramics (ferroelectrics–relaxor ferroelectrics–antiferroelectrics), glass-ceramics, thin and thick films, and polymer-based composites. The results indicate that lead-free dielectric materials with large maximum polarization, high breakdown electric field, small remnant polarization, and slim polarization-electric field loops are more appropriate for developing dielectric capacitors with high energy density and efficiency. However, some significant drawbacks in current lead-free dielectric materials hinder the energy storage performance of these materials. Based on this, we review herein some new strategies to improve the energy-storage capacity of dielectric materials.